Perancangan Video Animasi untuk Memperkenalkan Damar Kurung Gresik - Meindanu Dimas Prasetyo (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2021)
One of the artifacts in Gresik is Damar Kurung. Damar Kurung is a typical Gresik lantern art that can be found during Ramadan. However, the phenomenon of malaise culture resulted in a lack of knowledge and passive act for the younger generation to support the existence of local culture. For this reason, there are appropriate alternative media to introduce Damar Kurung, one of them is animation video. The method used is a qualitative method. Qualitative data is obtained through observation, interviews, and literature studies. Damar Kurung's animated video entitled